Kepemimpinan Organisasi Pendidikan Unggul (Jenis, Gaya, dan Model) - Nursyahrani Fahmin; Jamrizal Jamrizal; Kasful Anwar Us (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Leadership style is a typical leader's behavior pattern when influencing his subordinates, what the leader chooses to do, the way the leader acts in influencing group members forms a style. Leadership style in an organization has a role that really determines the success of achieving the goals of an organization, in fact leadership style is the nature of habits, temperament, character and personality that differentiates a leader in interacting with other people. With this leadership style, cooperation will be established and there will be a vision and mission to achieve common goals within educational institutions. The leadership model applied by a leader in managing an agency or organization must be able to influence, guide, encourage or motivate each member in achieving common goals.